Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3389/fnmol.2023.1115569
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture alleviates perioperative hypothalamus-pituitary-adrenal axis dysfunction via circRNA-miRNA-mRNA networks

Abstract: Electroacupuncture (EA) has long been used to alleviate surgery-induced hypothalamic–pituitary–adrenal axis dysfunction. However, its downstream gene targets in the brain remain unclear. The aim of the present study was to clarify the potential targets of EA based on RNA sequencing techniques (RNA-seq). Rats were divided into normal control (NC), hepatectomy surgery (HT), HT + EA, and HT + sham EA groups followed by RNA-seq of two representative nuclei in the hypothalamus and amygdala. Weighted Gene Co-express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“… 60 A growing number of clinical studies have been conducted to evaluate the efficacy and safety of EA and TEAS in the perioperative period and the related mechanism research has gradually penetrated the molecular level of the central neural system. 61 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 60 A growing number of clinical studies have been conducted to evaluate the efficacy and safety of EA and TEAS in the perioperative period and the related mechanism research has gradually penetrated the molecular level of the central neural system. 61 …”
Section: Discussionmentioning
confidence: 99%
“…60 A growing number of clinical studies have been conducted to evaluate the efficacy and safety of EA and TEAS in the perioperative period and the related mechanism research has gradually penetrated the molecular level of the central neural system. 61 In a word, this study analyzed the general information and identified the research hotspots and trends of acupuncture in perioperative medicine in the past decade by bibliometric analysis. Most research on the application of acupuncture in perioperative medicine focused on postoperative pain management and postoperative gastrointestinal functional recovery, especially for postoperative ileus and PONV.…”
Section: Research Trend Of Acupuncture In Perioperative Medicinementioning
confidence: 99%